Biblical-Pharmaceutical Study on Some Medications in Holy Scripture (Teología, 2021)
The following article presents a biblical-pharmaceutical study of some of the medicines that appear in Holy Scripture, offering basic, solid, scientifically-based historical-pharmaceutical knowledge. Only therapeutical drugs will be analyzed, specifically: wine, oil, salt, fig, fish gall and other minor mentions (mandrake, eye drops, etc.) will be pointed out. In each case, they will be compared out with old pharmacopoeias from various sources. Finally, some terms related to the pharma- cy are briefly presented.
Keywords: Bible; Pharmacy; Medications in the Bible; Ancient Pharmacopoeia.